Confidentiality of company's information: challenges for nominee directors - Hassan, Halyani (2015)
Company directors are subjected to certain fiduciary duties which have been discussed in length under the common law as well as in the statutory provisions. Directors’ fiduciary duties include duty to protect the confidentiality of company’s information. Any information which exclusively belong to the company are to be used only by the company for the company. Such information are considered as the property of the company and it must not be disclosed or used for the advantages of any person other than the company. The objective of this article is to discuss the duty of nominee director concerning the confidentiality of the company’s information. For the nominee directors who are actually represent their nominators on the board of directors, their duty would be challenging since they might be expected by their nominators to provide the latter with certain company’s information. In addition, the paper would also determine what amount to be confidential information. The study is based on doctrinal and statutory analysis of selected jurisdiction. It will analyse cases from various jurisdictions which discussed the extent of which this duty should be imposed upon the nominee directors. It is argued in our submission that the nominee directors are in vulnerable position by being directors and representing their nominators at the same time. Though it has been clearly legislated that their loyalty is to the company they should to a certain extent be allowed to disclose information which would not jeopardised their companies. Thus it would be necessary to identify in what circumstances and what kind of information could be revealed by the nominee directors.